Prevalence of Impostor Phenomenon among Employees in a Higher Education Institution: Implications for Faculty Development And Workplace Well-Being - Landingin, Queenne Kimverlee; Ramos, Belinda; Corpuz, Princess Jhoie (Technium Education and Humanities, 2026)
Impostor phenomenon (IP) has expanded across disciplines, but many professional contexts remain under-studied, including institutions of higher education. The study aims to examine the prevalence of impostor phenomenon among employees of the University of La Salette, Inc., which will help to provide a basis for future developments of institutional interventions, mentoring, and employees development initiatives, which constitute employees' well-being and professional growth, organizational efficiency, which further aims to promote the goal of sustainable quality education. The study employed a descriptive quantitative approach to eighty-four (84) employees who respondend to the Clance IP survey. The results revealed moderate impostor phenomenon (35.3%) among employees and younger ones from 1-10 years of experience, and full-time employees had moderate to frequent impostor experiences. Also, the results of the analysis found a significant difference when grouped according to their years of service (tenure). On the other hand, age, department, sex, and employment status showed no significant differences, indicating impostor feelings can affect diverse groups in the institution. Lastly, the findings show that while high impostor phenomenon is rare, many employees display moderate impostor feelings.